Review and Prospects of Human Resource Information Systems (HRIS) of Developing Countries in 21st Century - Aarzoo (International Journal of New Media Studies: International Peer Reviewed Scholarly Indexed Journal, 2023)
The role of Human resource management (HRM) has shifted overall from traditional (popularly called personnel management) to a strategic one. HRIS outline the amalgamation between HRM and IS. HRIS is one of the best neo teric HR tools in modern organizations. It became popular in developed coun tries since the beginning of this century. However, only few corporate organizations and MNCs in developing countries like Bangladesh have started to adopt and use HRIS since this decade. But still its adoption and usages are li mited to few mid to large sized organizations.